An unusual cause of hemoptysis due to leaking subclavian artery pseudoaneurysm secondary to trauma - Bhatt, Yugandhar; Md Abdul, Waseem; Zahera, Misba (International Journal of Research in Medical Sciences, 2017)
Pseudoneurysms of the subclavian artery after blunting thoracic trauma presenting with a complication of hemoptysis are rare, most of which occur early, within days of trauma and represent a challenging surgical problem. Only a few scattered case reports are found in the literature. Here, we present the case of a 36-year-old male, with a history of blunt injury to the chest with right clavicular fracture, a few years back, who presented with cough, hemoptysis and shortness of breath of five days duration. On complete evaluation it was found that these complaints were due to a sub clavian artery pseudo aneurysm in the proximal part, which is compressing on the right upper lobe bronchus and blood leaking into the parenchyma and airways producing the symptoms. He was managed conservatively and stabilized. Later aneurysm resection and anastomosis was done electively. The patient is now asymptomatic and healthy.